(untitled) (Texas Journal of Medical Science, 2026)
In this scientific study, the features of the histotopographic structure and morphometric parameters of deep lymph nodes in the neck of baby rats born from female rats receiving a research diet were studied. The results of the study show that rats born from rats that were fed a low-fat diet daily have deep lymph nodes. The dead formation occupies 58.1 % of the area, the primary lymphoid follicular zone – 14.7 %, the medulla – 22.3 %, the paracortical zone – 8.5 %. By the 20-day period, the area of the cavity decreased by 2 times, the primary follicular zone increased (18.3 %), the secondary follicular zone increased (11.6 %), and the paracortical area also expanded (13.4 %). By the 4-month period, it was observed that follicles have the same area, the area of secondary follicles increased (19.6 %) compared to primary follicles, and the paracortical follicle occupied 12.1 % of the area.